Functionalized Silver Nanoparticle-Decorated Paper Sensor for Rapid Colorimetric Detection of Copper Ions in Water - Budlayan, Marco Laurence M (Archīum Ateneo, 2021)
Copper contamination to water bodies is an environmental concern of significant risk due to its harmful effect on aquatic life forms and human beings. Herein, a paper-based colorimetric sensor was fabricated by immobilizing polyethyleneimine-capped silver nanoparticles (PEI-AgNPs) on commercial filter paper. The sensitivity and selectivity of the paper-based sensor's colorimetric response to copper ions in water were investigated. PEI-AgNPs with an average diameter of 12.66 ± 4.07 nm were successfully immobilized on the filter paper by the simple dipping technique, as evidenced by the scanning electron microscopy with energy-dispersive x-ray result. A color change from pale yellow to dark yellow green was noted after exposing the paper sensor in a water sample with copper ions. This colorimetric response was exclusively observed for copper ions only, suggesting the selectivity of the paper sensor towards copper ions. Moreover, ultraviolet–visible spectroscopy results revealed that the detection limit of the paper sensor was observed to about 1.0 ppm. Meanwhile, color analysis on the sensor's digital images revealed the linear response of the sensor with decreasing copper ion concentration down to 1.0 ppm. The selectivity of the sensor was also observed by the color intensity profile of the sensor. This work presents promising results that can be utilized as a reference for developing affordable, fast, portable, and reliable sensing devices for on-site water quality monitoring and other applications.